Microbial Diversity and Connectivity in Deep-Sea Sediments of the South Atlantic Polar Front - Varliero, Gilda; Bienhold, Christina; Schmid, Florian; Boetius, Antje; Molari, Massimiliano (Frontiers in Microbiology, 2019)
Ultraslow spreading ridges account for one-third of the global mid-ocean ridges. Their impact on the diversity and connectivity of benthic deep-sea microbial assemblages is poorly understood, especially for hydrothermally inactive, magma-starved ridges. We investigated bacterial and archaeal diversity in sediments collected from an amagmatic segment (10°−17°E) of the Southwest Indian Ridge (SWIR) and in the adjacent northern and southern abyssal zones of similar water depths within one biogeochemical province of the Indian Ocean. Microbial diversity was determined by 16S ribosomal RNA (rRNA) gene sequencing. Our results show significant differences in microbial communities between stations outside and inside the SWIR, which were mostly explained by environmental selection. Community similarity correlated significantly with differences in chlorophyll a content and with the presence of upward porewater fluxes carrying reduced compounds (e.g. ammonia, sulfide), suggesting that trophic resource availability is a main driver for changes in microbial community composition. At the stations in the SWIR axial valley (3655−4448 m water depth), microbial communities were enriched in bacterial and archaeal taxa common in organic matter-rich subsurface sediments (e.g. SEEP-SRB1, Dehalococcoida, Atribacteria, and Woesearchaeota) and chemosynthetic environments (mainly Helicobacteracaea). The abyssal stations outside the SWIR communities (3760−4869 m water depth) were dominated by OM1 clade, JTB255, Planctomycetaceae, and Rhodospirillaceae. We conclude that ultraslow spreading ridges create a unique environmental setting in sedimented segments without distinct hydrothermal activity, and play an important role in shaping microbial communities and promoting diversity, but also in connectivity among deep-sea habitats.